PENGUATAN PROGRAM BIMBINGAN PRA-NIKAH SEBAGAI UPAYA PENCEGAHAN PERCERAIAN USIA MUDA DI KUA KENCONG - Hakim, Faisol; Maulana, Puji; Munfaridah, Fitriyatul; Ilmi, Lita Nafilatul; Fitriani, Richma; Asna, Asna; Lubis, Ahmad Hafidz (Universitas Al-Falah As-Sunniyah Kencong Jember, 2025)
The high rate of divorce among young couples has become a concerning social issue, including in Kencong, Jember Regency. Based on data from the Kencong Religious Affairs Office (KUA), most divorce cases in 2023 involved couples around 21 years old, with primary causes including economic problems, social media influence, and pressure from extended families. This community service aims to support efforts to prevent early-age divorce by strengthening the pre-marital counseling program at KUA Kencong. The method used is the Asset-Based Community Development (ABCD) approach, which includes the stages of preparing, discovering, dreaming, defining, designing, and destiny. Activities were carried out through field observations, interviews with religious counselors, as well as mentoring and reinforcement of the existing pre-marital counseling program. The results indicate that strengthening this program has improved young couples’ awareness in preparing for marriage emotionally, spiritually, and socially. The implication of this activity is the need for sustainable collaboration between academics and the KUA to develop contextual and continuous educational programs that can reduce early-age divorce rates.